Think Pair Share VS Pair Check: Mana Yang Lebih Baik - risya novertie; sudjarwo sudjarwo; Risma MSinaga (Jurnal Studi Sosial / Journal of Social Studies, 2019)
Education is a form of dynamical culture and a condition for human development. As an educator, teachers do not only teach their students to know things, but also have to practice students skills, attitudes and mental. The skills, attitudes and mentalities are not only to be known, but also should be mastered and practiced by students in their daily lives. The objectives of the study were to find out the social skills differences between students whose learning by Think Pair Share (TPS) model and students whose learning by Pair Check (PC) model, to analyse  the effectiveness of the TPS and PC model in achieving social skills indicators in students who have high interest in study, and to analyse the interactions between learning models and learning interest.Pendidikan adalah salah satu bentuk perwujudan kebudayaan manusia yang dinamis dan syarat perkembangan. Sebagai seorang pendidik, guru tidak hanya mengajarkan siswanya untuk mengetahui berbagai hal. Guru juga harus melatih keterampilan, sikap dan mental anak didik. Penanaman keterampilan, sikap dan mental ini tidak bisa sekedar asal tahu saja, tetapi harus dikuasai dan dipraktikkan siswa dalam kehidupan sehari-harinya. Penelitian ini bertujuan untuk mengetahui perbedaan keterampilan sosial antara siswa yang pembelajarannya menggunakan model pembelajaran Think Pair Share (TPS) dengan model pembelajaran Pair Chek (PC), menganalisa keefektifan model pembelajaran TPS dan PC dalam mencapai indikator keterampilan sosial pada siswa yang memiliki minat belajar tinggi, serta menganalisa interaksi antara model pembalajaran dengan minat belajar.Kata kunci: keterampilan sosial, think pair share, pair check, pembelajaran IPS